A holistic perspective on planktonic communities across the Northwestern Mediterranean Sea - Magali Lescot; Nolan Lezzoche; Louise Laux; Sarah Romac; Loïc Guilloux; Elisabeth Chevillon; Corentin Bodson; Corinne Desnos; Amanda Elineau; Laëtitia Jalabert; Natalia Llopis Monferrer; Miguel Mendez Sandin; et al. (Frontiers in Marine Science, 2026)
The Northwestern Mediterranean Sea is undergoing rapid environmental changes driven by climate variability and intense anthropogenic pressure. To monitor and understand the long-term impacts on marine ecosystems, the Mediterranean Ocean Observing System for the Environment (MOOSE) program combines multidisciplinary observations, including physical, chemical, and biological data across temporal and spatial scales. This study presents a holistic assessment of planktonic communities across the Northwestern Mediterranean using integrated approaches—environmental genomics and high-resolution imaging—spanning all plankton size fractions and depths. Data collected during three MOOSE-GE cruises in 2017, 2018, and 2019 were analyzed to explore plankton diversity patterns in relation to oceanographic features. Plankton assemblages were primarily shaped by organism size and water column depth, with fractions of 0.2–3 and 3–180 µm in the surface and deep chlorophyll maximum layers showing the highest alpha diversity. Fractions > 64 µm were dominated by metazoans, particularly Arthropoda, whereas size classes collected by Niskin bottles were dominated by protists such as Syndiniales and Rhizaria. Differences among cruises and sampling periods were detected in Niskin bottle samples, especially for diatoms and dinoflagellates, while plankton tow samples exhibited less pronounced temporal variability. Physical clustering of stations revealed clear cross-shelf and basin-scale gradients, which aligned more closely with community structure at fine taxonomic resolution (OTU level) for small plankton. Integrating imaging with environmental genomic data enhanced the characterization of key taxa like Copepoda and Rhizaria, demonstrating the complementary strengths of each method. While imaging provided quantitative data, environmental genomics captured cryptic and morphologically indistinct taxa, emphasizing the value of molecular approaches for microbial plankton. This study highlights the critical importance of combining high-resolution molecular and imaging tools with detailed environmental context to unravel plankton biodiversity patterns. It demonstrates that depth, size, and taxonomic resolution are key dimensions for understanding community structure over time. The MOOSE program proves effective for ecosystem-scale monitoring, providing an essential foundation for future assessments of biogeochemical processes and ecosystem responses to climate change and human-induced alterations in the Mediterranean Sea.

Impact of internal tides on chlorophyll a distribution and primary production off the Amazon shelf from glider measurements and satellite observations - Amine M'hamdi; Ariane Koch-Larrouy; Alex Costa da Silva; Isabelle Dadou; Carina Regina de Macedo; Anthony Bosse; Vincent Vantrepotte; Habib Micaël Aguedjou; Trung-Kien Tran; Pierre Testor; Laurent Mortier; Arnaud Bertrand; et al. (Ocean Science, 2025)
The ocean region off the Amazon shelf including the shelf break presents a hotspot for internal tide (IT) generation, yet its impact on phytoplankton distribution remains poorly understood. While previous studies have extensively examined the physical characteristics and dynamics of ITs, their biological implications – particularly in nutrient-limited environments – remain underexplored. To address this question, we analyzed a 26 d glider mission deployed over September–October 2021 sampling hydrographic and optical properties (chlorophyll a) at high resolution along an IT pathway as well as satellite chlorophyll a and altimetry data to assess mesoscale interactions. Chlorophyll a dynamics were analyzed under varying IT intensities, comparing strong (HT) and weak (LT) internal tide conditions. Results reveal that ITs drive vertical displacements of the deep chlorophyll maximum (DCM) from 15 to 45 m, accompanied by 50 % expansion in its thickness during HT events. This expansion is observed with a dilution of the chlorophyll a maximum concentration within the DCM depth. While direct turbulence measurements were not collected, the observed vertical redistribution of chlorophyll a is indicative of tidally driven cross-isopycnal exchanges, the only physical mechanism explaining the transfer of biomass above and below the DCM. At the surface, turbulent fluxes provide 38 % of the chlorophyll a input, while the remainder is supplied by in situ biological activity. Notably, total chlorophyll a in the water column increases by 14 %–29 % during high internal tide phases, indicating a net enhancement of primary productivity driven by the combined effects of vertical mixing and stimulated surface-layer biological activity. These findings indicate that internal tides can be an important driver of chlorophyll a distribution and short-term biological variability in our study region. By reshaping the vertical chlorophyll a profile through vertical mixing, active internal tides influence primary productivity and may contribute to carbon cycling, particularly in oligotrophic oceanic environments where both a deep chlorophyll maximum and strong internal tides are present.

The Levantine Intermediate Water in the western Mediterranean and its interactions with the Algerian Gyres: insights from 60 years of observation - Katia Mallil; Pierre Testor; Anthony Bosse; Félix Margirier; Loic Houpert; Hervé Le Goff; Laurent Mortier; Ferial Louanchi (Ocean Science, 2022)
The presence of two large-scale cyclonic gyres in the Algerian Basin influences the general and eddy circulation, but their effects on water mass transfer remain poorly characterized. Our study has confirmed the presence of these gyres using the first direct current measurements of the whole water column collected during the SOMBA-GE2014 cruise, specifically designed to investigate these gyres. Using cruise sections and a climatology from 60 years of in situ measurements, we have also shown the effect of these gyres on the distribution at intermediate depth of Levantine Intermediate Water (LIW) with warmer (∼ 0.15 ∘C) and saltier (∼ 0.02) characteristics in the Algerian Basin than in the Provençal Basin. The Algerian Gyres, combined with the effect of anticyclonic Algerian Eddies, also impact horizontal density gradients with sinking of the isopycnals at the gyres' centers. Temporal cross-correlation of LIW potential temperature referenced to a signal observed southwest of Sardinia reveals a timescale of transit of 4 months to get to the center of the Algerian Basin. The LIW potential temperature and salinity trends, on average in the basin interior, are estimated to be +0.0022 ± 0.0002 ∘Cyr-1 and +0.0022 ± 0.0001 yr−1, respectively, over the 1968–2017 period and accelerating to +0.048 ± 0.003 ∘Cyr-1 and +0.0076 ± 0.0009 yr−1 over the 2013–2017 period.

Ocean Integration: The Needs and Challenges of Effective Coordination Within the Ocean Observing System - Adèle Révelard; Joaquín Tintoré; Jacques Verron; Pierre Bahurel; John A. Barth; Mathieu Belbéoch; Jérôme Benveniste; Pascal Bonnefond; Eric P. Chassignet; Sophie Cravatte; Fraser Davidson; Brad deYoung; et al. (Frontiers in Marine Science, 2022)
Understanding and sustainably managing complex environments such as marine ecosystems benefits from an integrated approach to ensure that information about all relevant components and their interactions at multiple and nested spatiotemporal scales are considered. This information is based on a wide range of ocean observations using different systems and approaches. An integrated approach thus requires effective collaboration between areas of expertise in order to improve coordination at each step of the ocean observing value chain, from the design and deployment of multi-platform observations to their analysis and the delivery of products, sometimes through data assimilation in numerical models. Despite significant advances over the last two decades in more cooperation across the ocean observing activities, this integrated approach has not yet been fully realized. The ocean observing system still suffers from organizational silos due to independent and often disconnected initiatives, the strong and sometimes destructive competition across disciplines and among scientists, and the absence of a well-established overall governance framework. Here, we address the need for enhanced organizational integration among all the actors of ocean observing, focusing on the occidental systems. We advocate for a major evolution in the way we collaborate, calling for transformative scientific, cultural, behavioral, and management changes. This is timely because we now have the scientific and technical capabilities as well as urgent societal and political drivers. The ambition of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030) and the various efforts to grow a sustainable ocean economy and effective ocean protection efforts all require a more integrated approach to ocean observing. After analyzing the barriers that currently prevent this full integration within the occidental systems, we suggest nine approaches for breaking down the silos and promoting better coordination and sharing. These recommendations are related to the organizational framework, the ocean science culture, the system of recognition and rewards, the data management system, the ocean governance structure, and the ocean observing drivers and funding. These reflections are intended to provide food for thought for further dialogue between all parties involved and trigger concrete actions to foster a real transformational change in ocean observing.

Valuing the Ocean Carbon Sink in Light of National Climate Action Plans - Johannes Karstensen; Wilfried Rickels; Pierre Testor; Maciej Telszewski (Oceanography, 2021)

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Future Vision for Autonomous Ocean Observations - Christopher Whitt; Jay Pearlman; Brian Polagye; Frank Caimi; Frank Muller-Karger; Andrea Copping; Heather Spence; Shyam Madhusudhana; William Kirkwood; Ludovic Grosjean; Bilal Muhammad Fiaz; Satinder Singh; et al. (Frontiers in Marine Science, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Challenges for Sustained Observing and Forecasting Systems in the Mediterranean Sea - Joaquín Tintoré; Nadia Pinardi; Enrique Álvarez-Fanjul; Eva Aguiar; Diego Álvarez-Berastegui; Marco Bajo; Rosa Balbin; Roberto Bozzano; Bruno Buongiorno Nardelli; Vanessa Cardin; Benjamin Casas; Miguel Charcos-Llorens; et al. (Frontiers in Marine Science, 2019)

Evolving and Sustaining Ocean Best Practices and Standards for the Next Decade - Jay Pearlman; Mark Bushnell; Laurent Coppola; Johannes Karstensen; Pier Luigi Buttigieg; Francoise Pearlman; Pauline Simpson; Michele Barbier; Frank E. Muller-Karger; Cristian Munoz-Mas; Peter Pissierssens; Cyndy Chandler; et al. (Frontiers in Marine Science, 2019)

Synergy between in situ and altimetry data to observe and study Northern Current variations (NW Mediterranean Sea) - Alice Carret; Florence Birol; Claude Estournel; Bruno Zakardjian; Pierre Testor (Ocean Science, 2019)
During the last 15 years, substantial progress has been achieved in altimetry data processing, now providing data with enough accuracy to illustrate the potential of these observations for coastal applications. In parallel, new altimetry techniques improve data quality by reducing land contamination and enhancing the signal-to-noise ratio. Satellite altimetry provides more robust and accurate measurements ever closer to the coast and resolve shorter ocean signals. An important issue is now to learn how to use altimetry data in conjunction with other coastal observing techniques. Here, we cross-compare and combine the coastal currents provided by large datasets of ship-mounted acoustic Doppler current profilers (ADCPs), gliders, high-frequency (HF) radars and altimetry. We analyze how the different available observing techniques, with a particular focus on altimetry, capture the Northern Current variability at different timescales. We also study the coherence, divergence and complementarity of the information derived from the different instruments considered. Two generations of altimetry missions and both 1 Hz and high-rate measurements are used: Jason-2 (nadir Ku-band radar) and SARAL/AltiKa (nadir Ka-band altimetry); their performances are compared. In terms of mean speed of the Northern Current, a very good spatial continuity and coherence is observed at regional scale, showing the complementarity among the types of current measurements. In terms of current variability, there is still a good spatial coherence but the Northern Current amplitudes derived from altimetry, glider, ADCP and HF radar data differ, mainly because of differences in their respective spatial and temporal resolutions. If we consider seasonal variations, 1 Hz altimetry captures ∼60 % and ∼55 % of the continental slope current amplitude observed by the gliders and by the ADCPs, respectively. For individual dates this number varies a lot as a function of the characteristics of the Northern Current on the corresponding date, with no clear seasonal tendency observed. Compared to Jason-2, the SARAL altimeter data tend to give estimations of the NC characteristics that are closer to in situ data in a number of cases. The much noisier high-rate altimetry data appear to be more difficult to analyze but they provide current estimates that are generally closer to the other types of current measurements. Thus, satellite altimetry provides a synoptic view of the Northern Current circulation system and variability, which helps to interpret the other observations. Its regular sampling allows for the observation of many features that may be missed by irregular in situ data.

Characterizing, modelling and understanding the climate variability of the deep water formation in the North-Western Mediterranean Sea - Samuel Somot; Loic Houpert; Florence Sevault; Pierre Testor; Anthony Bosse; Isabelle Taupier-Letage; Marie-Noelle Bouin; Robin Waldman; Christophe Cassou; Emilia Sanchez-Gomez; Xavier Durrieu de Madron; Fanny Adloff; et al. (Climate Dynamics, 2018)

Sensitive Determination of the Dissolved Phosphate Pool for an Improved Resolution of Its Vertical Variability in the Surface Layer: New Views in the P-Depleted Mediterranean Sea - Kahina Djaoudi; France Van Wambeke; Laurent Coppola; Fabrizio D'Ortenzio; Sandra Helias-Nunige; Patrick Raimbault; Vincent Taillandier; Pierre Testor; Thibaut Wagener; Elvira Pulido-Villena (Frontiers in Marine Science, 2018)

An International Perspective on Graduate Education in Physical Oceanography - Holger Brix; James Hench; Helen Johnson; Shaun Johnston; Jeff Polton; Moninya Roughan; Pierre Testor (Oceanography, 2003)